Implementasi Instagram Ads dalam Strategi Digital Marketing Warung Kopitiam Dolly - Melur Tri Swastika; Hapsari, Indria Dwi; Laily , Nadya Faizatul; Husaini, Aurelia Reyza Safitri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the national economy but face challenges in digital marketing. This study aims to improve customer engagement and competitiveness of Warung Kopitiam Dolly in Jember with a digital marketing strategy through Instagram Ads. The methods used include digital marketing training for owners and employees, designing attractive visual-based content, and implementing Instagram Ads as a promotional media. The results of the study showed a significant increase in the number of Instagram followers from 833 to more than 1,000 in six months, an increase in customer interaction from 50 to 70 interactions per post, and an increase in the number of visitors to the shop by 30%. In addition, there was an increase in average daily sales which increased by around 67%. The evaluation results showed that this training succeeded in improving the digital marketing skills of owners and employees, enabling them to implement digital marketing strategies sustainably. Thus, social media-based marketing has proven effective in supporting the growth of MSMEs in the culinary sector.